The Phenomenon of Kampung in Surabaya in Defensible Space Perspective: Case Study on Kampung Tambaksari Surabaya - Tri Dani Widyastuti (JURNAL SOSIAL HUMANIORA (JSH), 2023)
Kampungs, simple settlement units commonly found in Indonesian cities, including Surabaya, play a significant role in the city's development, preserving its identity as a metropolitan city with a strong foundation rooted in these traditional communities. Surabaya recognizes the importance of kampungs and their contribution, evident from the existence of around 5000 kampungs within the city. However, being a bustling metropolitan center, Surabaya also faces its fair share of crime-related challenges. One theory that addresses the relationship between crime and the built environment is the defensible space theory. To explore this further, a study examines Tambaksari, a kampung within Surabaya, in the context of the current defensible space theory. This investigation employs an in-depth observation method to gather specific data on Tambaksari as a single case, aiming to provide valuable insights for stakeholders to formulate more targeted policies that enhance the development of kampungs in Surabaya while effectively addressing crime-related issues.